Analisis Potensi Kya-Kya Kembang Jepun Sebagai Objek Wisata Kuliner Di Kota Surabaya - Amelia Putri Divindha; Santi Isnaini (Jurnal Ilmiah Wahana Pendidikan, 2023)
Culinary is currently known as one of the potentials of a tourist destination. Culinary has an important role in the tourism industry because most tourist spending is for food and beverages. In 2017, it was recorded that the culinary sector alone reached a percentage of around 30-40 percent of the sector spent by tourists in Indonesia. The diversity of culinary types found in Surabaya City, East Java has great potential to be culinary tourism potential. When tourists come and want to do culinary tourism in the city of Surabaya, with the current situation in the field it is realized that if you want to have a culinary tour of Surabaya's diverse specialties, it cannot be done in one place easily, but is scattered in various remote places. Therefore, it is necessary to plan a typical Surabaya Regional Culinary Tourism Center as an alternative tourist attraction that presents various kinds of Surabaya's culinary and as a place to visit to enjoy a culinary in Surabaya. This study aims to analyze the potential of Kya-Kya Kembang Jepun as a culinary tourist attraction in Surabaya City. This research is qualitative research, the analysis method used is SWOT analysis. The results showed that culinary tourism in the Kya-Kya has considerable potential to become a culinary tourism destination that can attract tourists to visit.